2019
DOI: 10.1021/acs.energyfuels.9b01106
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of NO and SO2 from Exhaust Gas by Cyclic Scrubbing and Online Supplementing pH-Buffered NaClO2 Solution

Abstract: Experiments were conducted to simultaneously remove NO and SO2 from simulated exhaust gas by cyclic scrubbing and online supplementing pH-buffered NaClO2 solutions in a bench-scale reactor. The effects of key operating parameters on pollutant removal performance had been investigated. The results suggested that an extremely high oxidant utilization rate could be obtained when the oxidant supplementing molar rate approached the oxidant consumption molar rate. Though co-existing SO2 in flue gas would consume a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…al. on NO removal using NaClO2 between the pH of 2.4 to 8.0 also showed that the absorption of NO2 that was formed from the oxidation of NO was highest at pH 8.0 (Han et al 2019).…”
Section: Analysis Of Aqueous Solutionmentioning
confidence: 84%
See 1 more Smart Citation
“…al. on NO removal using NaClO2 between the pH of 2.4 to 8.0 also showed that the absorption of NO2 that was formed from the oxidation of NO was highest at pH 8.0 (Han et al 2019).…”
Section: Analysis Of Aqueous Solutionmentioning
confidence: 84%
“…Since the acceptance of wet scrubbers on-board ships has already gained much traction, it is justifiable to explore its potential to remove NOx on top of SOx. Already in the R&D scene, there are many upcoming methods for treating SOx and NOx simultaneously (Chang et al 2004;Chu et al 2001;Cui et al 2018;Cui et al 2019;Deshwal et al 2008;Fang et al 2013;Fang et al 2011;Han et al 2019;Hao et al 2017;Hao et al 2016;Kang et al 2020;Kang et al 2018;Liémans and Thomas 2013;Liu et al 2014;Liu et al 2018;Mondal and Chelluboyana 2013;Park et al 2015;Wang et al 2015;Xi et al 2020;Xie et al 2019;Yan et al 2020;Yang et al 2016;Yang et al 2018;Zhao et al 2010;Zhao et al 2015). Apart from the marine sector, the industry involving land-based small and medium sized coal-fired boilers are also actively researching this area due to shortcomings encountered in existing control technologies (Kang et al 2020;Shao et al 2019;Sun et al 2015;Wu et al 2018;Xie et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, high-concentration NaOH would decrease or impede NO absorption. The results of Chan [6] and Brogren, Karlsson, and Bjerle [7] showed that the NaClO2 oxidation method showed a high removal rate for both SO 2 and NO. The results of Hsu, Lee, and Chou [8] and Chien, Chu, and Hsueh [9] showed that the reaction temperature of desulfurization and denitrification of the NaClO 2 solution was between 20~30°C and the removal reactions were as follows: (1) NaClO 2 is decomposed in an acid solution:…”
Section: Introductionmentioning
confidence: 97%
“…It is the key point to oxidize NO to the more soluble NO 2 and N 2 O 5 by suitable oxidants at low temperature. A lot of studies have been conducted on various oxidants, such as H 2 O 2 , ozone (O 3 ), NaClO, NaClO 2 and persulfate salts 8‐12 . Among them, O 3 was considered as an effective and promising oxidant, owing to its strong oxidizing ability.…”
Section: Introductionmentioning
confidence: 99%